Antara Tradisionalitas Dan Modernitas: Membangun Paradigma Kemajuan Umat Islam Melalui Integrasi Epistemologi Barat Dan Islam - Tirta, Tirta Alim Wiliam Diaz (Program Studi Aqidah dan Filsafat Islam STISA Ash-Shofa Tasikmalaya, 2024)
This journal discusses the challenge of integrating tradition and modernity within the context of advancing the Muslim community in the era of globalization. By proposing a new paradigm that combines Islamic and Western epistemology, this study aims to explore how moral and ethical values can be integrated into education to develop competent and integrity-driven young leaders. The method used in this research includes a literature review and comparative analysis of educational practices in the Muslim world and Western scientific approaches. The findings indicate that education focused on critical thinking, innovation, and collaboration across various sectors can provide relevant solutions to contemporary challenges. Additionally, through intercultural dialogue and active participation in social and political dynamics, Muslims can build a more inclusive and progressive society. The conclusion of this study confirms that this new paradigm not only addresses the challenges faced by Muslims but also contributes to building a more harmonious and sustainable world.